THE IMAGE OF WOMAN IN ENGLISH LITERATURE: JANE AUSTEN, CHARLOTTE BRONTË, AND VIRGINIA WOOLF - E. B. Tasheva (International Journal of Literature and Language Studies, 2026)
This article examines the evolution of the female image in English literature through the works of Jane Austen, Charlotte Brontë, and Virginia Woolf. The study argues that the literary representation of woman changes from a socially regulated subject in Austen, to a morally and emotionally self-defining heroine in Brontë, and finally to a modernist consciousness in Woolf. The article focuses on the connection between female character, narrative voice, social space, education, marriage, economic dependence, and inner freedom. By comparing Elizabeth Bennet, Jane Eyre, and Woolfian female figures, the research demonstrates that English literature gradually transformed the woman from an object of social expectation into an active interpreter of her own existence. The image of woman is therefore not merely a thematic element but a structural principle through which English prose explores ethics, identity, and cultural change.